Formulation of Zero-Trans Crystalized Fats Produced from Palm Stearin and High Oleic Safflower Oil Blends - Nydia E. Buitimea-Cantúa; María Guadalupe Salazar-García; Reyna Luz Vidal-Quintanar; Sergio O. Serna-Saldívar; Refugio Ortega-Ramirez; Génesis Vidal Buitimea-Cantúa (Journal of Food Quality)
High intake of trans fat is associated with several chronic diseases such as cardiovascular disease and cancer. Fat blends, produced by direct blending process of palm stearin (PS) with high oleic safflower oil (HOSO) in different concentrations, were investigated. The effects of the PS addition (50, 70, or 90%) and the rate of agitation (RA) (1000, 2000, or 3000 rpm) on physical properties, fatty acid profile (FAP), trans fatty acids (TFA), crystal structure, and consistency were researched. The blend containing 50% of each sort of oil (50% PS/50% HOSO) showed that melting point and features were similar to the control shortening. The saturated fatty acids (SFA) were higher followed by monounsaturated (MUFA) and polyunsaturated fatty acids (PUFA). Significant differences in the content of palmitic and oleic acids among blends were observed. The 50% PS/50% HOSO blend contained higher oleic acid (42.9%) whereas the 90% PS/10% HOSO was higher in palmitic acid (56.9%). The blending of PS/HOSO promoted the β crystal polymorphic forms. The direct blending process of equal amounts of PS and HOSO was an adequate strategy to formulate a new zero-trans crystallized vegetable fats with characteristics similar to commercial counterparts with well-balanced fats rich in both omega 3 and omega 6 fatty acids.